Exploring ethical dimensions of environmental sustainability and use of AI - Kannan, Hemachandran 1985-; Villamarin Rodriguez, Raul; Zoltay Paprika, Zita 1957-; Ade-Ibijola, Abejide (Advances in environmental engineering and green technologies (AEEGT) book series, 2024)
Exploring Ethical Dimensions of Environmental Sustainability and Use of AI is a comprehensive and insightful book that delves into the ethical implications and challenges that emerge at the intersection of environmental sustainability and the utilization of artificial intelligence (AI). With a focus on key ethical dimensions such as transparency, equity, privacy, autonomy, unintended consequences, and trade-offs, this book aims to provide a thorough understanding of the responsible deployment and development of AI in the realm of environmental sustainability.By addressing the ethical aspects and challenges involved, this book contributes to the development of ethical guidelines and frameworks that align AI technologies with the vision of a sustainable and equitable future. Researchers will find immense value in this book as it offers a holistic exploration of the ethical implications, filling a critical gap in the existing literature. Policymakers can gain valuable insights to inform the creation of ethical guidelines and regulations governing AI use in sustainable initiatives. Practitioners, including professionals working in environmental organizations or technology companies, will acquire practical knowledge to guide their decision-making and implementation of AI-driven solutions.